THE EFFECT OF CUSTOMER KNOWLEDGE AND PRODUCT UNIQUENESS ON PURCHASE INTENTION OF FASHION NFT - Saputra, I Gusti Putu Aditya; Salehudin, Imam (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.08.TAHUN.2024, 2024)
Non Fungible Tokens (NFT), which is a digital asset, are now starting to be widely used by brands in their marketing strategies to get closer to younger generation consumers. This new technology can bridge the digital world with physical products and form community for brands. The popularity of NFTs has increased in recent years due to cryptocurrency trend and the purchase of NFTs by celebrities. The aim of this research is to analyze the relationship between customer knowledge and product uniqueness on purchase intention for NFT fashion products. This research was conducted on 307 respondents in Indonesia who knew about NFT fashion and the brands that own these products. The research hypothesis was tested using the Structural Equation Modeling (SEM) method. The results of this research show a positive and significant relationship between customer knowledge and product uniqueness on purchase intention. Apart from that, product uniqueness was found to mediate the relationship between customer knowledge and purchase intention. The results of the findings in this research have implications for developing NFTs and brands more effectively, both in theory and practice.